2021
DOI: 10.1248/bpb.b21-00589
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Pharmacokinetics and Haematotoxicities of Aniline and Its Dimethyl Derivatives Orally Administered in Rats

Abstract: Aniline and its dimethyl derivatives reportedly become haematotoxic after metabolic N-hydroxylation of their amino groups. The plasma concentrations of aniline and its dimethyl derivatives after single oral doses of 25 mg/kg in rats were quantitatively measured and semi-quantitatively estimated using liquid chromatography-tandem mass spectrometry. The quantitatively determined elimination rates of aniline; 2,4-dimethylaniline; and 3,5-dimethylaniline based on rat plasma versus time curves were generally rapid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…We could successfully generate PBPK model input parameters for rat models calculated from a small number of chemical properties by machine-learning prediction tools. 26) Rat PBPK modeling 31) will also make increasingly important contributions to computational toxicology and facilitate assessment of the potential risks of industrial or food chemicals. In terms of human PBPK modeling, the previously used ridge regression approach 32) is a method for estimating the coefficients of multiple-regression models.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We could successfully generate PBPK model input parameters for rat models calculated from a small number of chemical properties by machine-learning prediction tools. 26) Rat PBPK modeling 31) will also make increasingly important contributions to computational toxicology and facilitate assessment of the potential risks of industrial or food chemicals. In terms of human PBPK modeling, the previously used ridge regression approach 32) is a method for estimating the coefficients of multiple-regression models.…”
Section: Resultsmentioning
confidence: 99%
“…8,9) Simplified PBPK models that use some fixed physiological system parameters are easier to handle than full PBPK models and are of use in the fields of drug discovery, poisoning, or therapeutic drug monitoring 7,[10][11][12] as well as in risk assessment for a variety of general chemicals or food components/additives. 13) Although the metabolic profiles of disparate chemicals (including aromatic amines 14,15) ) traditionally have been elucidated in rodent studies, 16) so-called new alternative methods (NAMs) for evaluating chemical safety have been widely investigated using in silico or in vitro approaches. 17,18) The approach that applies simple PBPK modeling, without any reference to experimental pharmacokinetic data, has the potential to play significant roles in replacing and reducing the use of animals for estimating toxicokinetics or internal exposures of drugs, food components, and general chemicals.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the tolerable daily intake (TDI) value of aniline has been set by the United States Environmental Protection Agency at 7.0 µg/kg/day (Chinthakindi and Kannan, 2022b). Aniline and 2,6-dimethylaniline are both metabolized to hematotoxic N-hydroxylated metabolites and excretable glucuronide conjugates of their amino groups (Miura et al, 2021a;Lewalter and Korallus, 1985;Gonçalves et al, 2001). Aromatic amines, including aniline and 2,6-dimethylaniline, have been detected in indoor Correspondence: Hiroshi Yamazaki (E-mail: hyamazak@ac.shoyaku.ac.jp) air, cigarette smoke, and indoor dust collected in several countries (Chinthakindi and Kannan, 2021;Stabbert et al, 2003;Zhang et al, 2017;Palmiotto et al, 2001;Kannan, 2022b, 2022a).…”
Section: Introductionmentioning
confidence: 99%
“…Physiologically based pharmacokinetic (PBPK) modeling is a generally recognized method for estimating toxicokinetics (Wambaugh et al, 2015(Wambaugh et al, , 2018Sayre et al, 2020). Simplified PBPK models constructed using chemical receptor, metabolizing, excreting, and central compartments have been developed for a range of substances and species (Miura et al, 2021a(Miura et al, , 2020b(Miura et al, , 2021b. The elimination rate of 2,6-dimethylaniline from rat plasma was slower than that of aniline, and we previously demonstrated that differences in the pharmacokinetics of aniline and its dimethyl derivatives in rats estimated by PBPK modeling were related to the existence of a methyl group at the C 2 -position (Miura et al, 2021a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation